Systematic review of avian hatching failure and implications for conservation - Marshall, Ashleigh F.; Balloux, François; Hemmings, Nicola; Brekke, Patricia (Biological reviews of the Cambridge Philosophical Society, 2023)
ABSTRACT Avian hatching failure is a widespread phenomenon, affecting around 10% of all eggs that are laid and not lost to predation, damage, or desertion. Our understanding of hatching failure is limited in terms of both its underpinning mechanisms and its occurrence across different populations. It is widely acknowledged that rates of hatching failure are higher in threatened species and in populations maintained in captivity compared to wild, non‐threatened species, but these differences have rarely been quantified and any broader patterns remain unexplored. To examine the associations between threat status, management interventions, and hatching failure across populations we conducted a phylogenetically controlled multilevel meta‐analysis across 231 studies and 241 species of birds. Our data set included both threatened (Critically Endangered, Endangered, and Vulnerable) and non‐threatened (Near Threatened and Least Concern) species across wild and captive populations, as well as ‘wild managed’ (‘free‐living’) populations. We found the mean overall rate of hatching failure across all populations to be 16.79%, with the hatching failure rate of wild, non‐threatened species being 12.40%. We found that populations of threatened species experienced significantly higher mean hatching failure than populations of non‐threatened species. Different levels of management were also associated with different rates of hatching failure, with wild populations experiencing the lowest rate of hatching failure, followed by wild managed populations, and populations in captivity experiencing the highest rate. Similarly, populations that were subject to the specific management interventions of artificial incubation, supplementary feeding, and artificial nest provision displayed significantly higher rates of hatching failure than populations without these interventions. The driver of this correlation between hatching failure and management remains unclear, but could be an indirect result of threatened species being more likely to have lower hatching success and also being more likely to be subject to management, indicating that conservation efforts are fittingly being focused towards the species potentially most at risk from extinction. This is the most comprehensive comparative analysis of avian hatching failure that has been conducted to date, and the first to quantify explicitly how threat status and management are associated with the rate of hatching failure in a population. We discuss the implications of our results, focusing on their potential applications to conservation. Although we identified several factors clearly associated with variation in hatching failure, a significant amount of heterogeneity was not explained by our meta‐analytical model, indicating that other factors influencing hatching failure were not included here. We discuss what these factors might be and suggest avenues for further research. Finally, we discuss the inconsistency in how hatching failure is defined and reported within the literature, and propose a standardised definition to be used in future studies which will enable better comparison across populations and ensure that the most accurate information is used to support management decisions.